Effects of soy consumption on serum estrogen level of girls - Koochakpoor, G; Mehran, SH; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Breast cancer is one of the most common malignancies in the world. Since this disease is hormone-related and its incidence is much lower in oriental population, it suggests a hypothesis that soy products may have an effect on hormonal status and, thereby on the incidence of breast cancer. The purpose of this before-after clinical trial was to determine the effects of soy on the levels of serum estrogen. Material and Methods 10 healthy girls between 20 and 25 living in dormitory were selected for 3 one-cycle phases of the study. They were single with normal menstrual cycle and no experience of alcohol, cigarette and soy consumption. The participants followed their regular diet in the first phase and the levels of their hormones were measured at 3rd, 13th and 23rd day of their cycle. In the second phase, 40 grams of Sobhan soy, a brand of soy in the market, were added to their diet and the same measurements were taken. At the final phase, the regular diet with no soy was followed with hormonal measurements by ELIZA method. In each phase, the weights of participants were measured with a digital scale (Seca). The validities of instruments were verified by choosing standard and authorized brands and samples in the kits were used for calibration. Data were analyzed by N4 software (ver. 4) and SPSS package (ver. 11.5). Findings Serum estrogen levels showed no significant differences between the phases of the study. Conclusion Consumption of soy in a month may not be a useful measure to change hormonal levels in young girls. Keywords: Breast cancer, Estrogen, Soy. *Corresponding Author: Koochkpoor, Gelare, Alumnus, Faculty of Nutrition and Food Sciences, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: glarekoochakpoor@yahoo.com